Assessment of Integral Indicators of the Surface Skating of the Rail Head in Sections of Speed and High Speed Train Traffic - Lesov, K.S. (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the condition of the surface skating of the rail head in sections of high-speed and high-speed train traffic to assess the integral indicators of the surface skating of the rails (long waves, medium waves, short waves).